Factors Affecting Listening Comprehension - Zia Syahreza; Syamsul Bahri Ys; Nira Erdiana (Universitas Syiah Kuala, 2020)
Students who enroll in the English Department are taught by the lecturers by using English. Therefore, the skill of listening is the main and the most important aspect needed to figure out teacher’s meaning. Relating to students listening comprehension, they encountered some difficulties. Thus, the aim of this study is to find out what factors affect students’ listening comprehension in the English Department of Syiah Kuala University. This study was conducted at English Department of Teacher Training and Education faculty of Syiah Kuala University. 20 Seventh semester students of English Department were selected as sample of this study. The method of this study was a quantitative descriptive study. The writer used a questionnaire which consist of 43 questions as an instrument of this study. The result of questionnaire become the main data of this study. The data was calculated by using statistical formula. The result of this study revealed that the most dominant factor affecting students’ listening comprehension skill was physical setting factor, 32%out of 100% followed by failure to concentrate factor (23%), content of Listening text factor (20%), Psychological characteristic factor (19%), speaker factor (14%), listener factor (10%), and linguistics feature (9%) lastly. Therefore, it is recommended for head office of English Department of Teacher Training and Education Faculty of Syiah Kuala University to upgrade the equipment used to conduct listening activity.